Pengaruh Beban Kerja dan Work-Life Balance terhadap Kepuasan Kerja Guru di SMPN XYZ - Sherlyna Wati, Eliya; Khaerul Rizal Abdurahman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of workload and work-life balance on teacher job satisfaction at XYZ Junior High School. The study's background is based on the phenomenon of high teacher absenteeism, which reflects job dissatisfaction. The research approach used was quantitative, with descriptive and associative methods. The study population included all 31 non-structural teachers at XYZ Junior High School who served as respondents. Data were collected through questionnaires and analyzed using validity and reliability tests, as well as multiple linear regression using SPSS version 27 software. The results showed that workload and work-life balance had a positive and significant effect on job satisfaction, both partially and simultaneously. The coefficient of determination (R²) of 0.523 indicates that the two independent variables explained 52.3% of the variation in teacher job satisfaction, while the remaining 47.7% was influenced by factors outside the research model. These findings emphasize the importance of proportional workload management and support for work-life balance as effective strategies for improving the well-being and professional satisfaction of educators. Keywords: Workload, Work-Life Balance, Job Satisfaction